Optimization of the purification of nucleocapsid protein of newcastle disease virus by ultracentrifugation method - Ahmad Raus, Raha; Yusof, Faridah (Journal of Pure and Applied Microbiology, 2014)
Protein purification is a process to remove impurities contains in a complex mixture and may involves a single step or by a combination of several steps. In this study, nucleocapsid (NP) protein of Newcastle disease virus (NDV) was purified using various purification steps from recombinant Escherichia coli. The purification steps involved ammonium sulphate precipitation, dialysis and sucrose gradient ultracentrifugation. In this study, the optimized condition for obtaining the highest NP protein yield in the final step of purification (ultracentrifugation) was determined. Two independent parameters which are centrifugal force and running time were manipulated and investigated. The optimum processing condition was determined by employing Face Centred Composite Design (FCCD) under Response Surface Method (RSM). Based on the almost fully elliptical plot showed in 2D and 3D response graphs, the optimum condition for obtaining the highest NP protein yield is near to the centre points of the response surface (condition of 159000xg or 31,000rpm and 5 hours). Although the optimum time to purify the highest NP protein yield is five hours centrifugation, the NP protein could also be purified after three hours centrifugation albeit with slight reduction in the yield. Less centrifugation time is important as pre- and post-centrifugation procedures for sucrose gradient ultracentrifugation is time consuming and laborious.